Cucumber fruit nutrient quality as influenced by variety and organic fertiliser rate - Makinde Eyitayo Adekunle; Alarima Iyabo Modupe; Ayeni Olawale Sunday; Shittu Taofik Akinyemi (Agricultura Tropica et Subtropica)
The nutrient contents of a product can depend on the quantity of fertiliser supplied. An experiment was conducted at the Federal University of Agriculture, Abeokuta, in the tropical rainforest‑savannah transitional zone of southwestern Nigeria to determine the nutrient contents of three cucumber varieties as influenced by Gateway Organic Fertiliser (GOF) rates. There were 48 plots of 3.0 × 2.0 m each, separated by 1.0 m pathways. The main plot was cucumber variety (Marketmore, Poinsett, and Marketer) while the sub‑treatment was organic fertiliser rate at 0, 5, 10, and 15 t.ha−1 in a split‑plot arrangement fitted into Randomised Complete Block Design (RCBD) with 4 replicates. Fruit nutrient contents differed with cucumber varieties and rates of gateway organic fertiliser. Marketmore variety fruits without application of GOF had higher moisture contents. Poinsett variety fruits cultivated with the application of 5 t. ha−1 GOF had higher dry matter contents. Poinsett variety fruits cultivated with either 10 or 15 t. ha−1 GOF had higher crude protein and carbohydrate contents when compared with other interactions. Poinsett variety cultivated with either 10 or 15 t. ha−1 GOF had higher vitamins A and C contents when compared with other interactions. It was concluded that cultivating the Poinsett cucumber variety with a 10 t.ha−1 GOF rate gave optimum nutrient contents concerning the crude protein, carbohydrate, and vitamin content. The Poinsett cucumber variety cultivated with 10 t. ha−1 Gateway Organic Fertiliser is recommended for optimum nutrient contents.